Cyber Crime Investigator's Field Guide - Middleton, Bruce (Milton : Auerbach Publishers, Incorporated, 2022)
Transhumanism, Artificial Intelligence, the Cloud, Robotics, Electromagnetic Fields, Intelligence Communities, Rail Transportation, Open-Source Intelligence (OSINT)--all this and more is discussed in Cyber Crime Investigator's Field Guide, Third Edition. Many excellent hardware and software products exist to protect our data communications systems, but security threats dictate that they must be all the more enhanced to protect our electronic environment. Many laws, rules, and regulations have been implemented over the past few decades that have provided our law enforcement community and legal system with the teeth needed to take a bite out of cybercrime. But there is still a major need for individuals and professionals who know how to investigate computer network security incidents and can bring them to a proper resolution. Organizations demand experts with both investigative talents and a technical knowledge of how cyberspace really works. The third edition provides the investigative framework that needs to be followed, along with information about how cyberspace works and the tools that reveal the who, where, what, when, why, and how in the investigation of cybercrime. Features New focus area on rail transportation, OSINT, medical devices, and transhumanism / robotics Evidence collection and analysis tools Covers what to do from the time you receive "the call," arrival on site, chain of custody, and more This book offers a valuable Q&A by subject area, an extensive overview of recommended reference materials, and a detailed case study. Appendices highlight attack signatures, Linux commands, Cisco firewall commands, port numbers, and more.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Networking / Security; COMPUTERS / Cryptography; COMPUTERS / Internet / Security